2007
DOI: 10.17305/bjbms.2007.3050
|View full text |Cite
|
Sign up to set email alerts
|

Electroneurography of Right Median and Ulnar Nerves in Diabetic Patients With and Without Retinopathy

Abstract: In this study we examined motor and sensory conduction velocities in right median and ulnar nerves in diabetic patients. Control group consisted of 25 healthy volunteers (13 males) with average age of 52 years. The first examined group consisted of 25 diabetic patients (13 males) without retinal changes, 59,6 years old on average, and the second group consisted of 40 patients (15 males) 59,4 years old on average: 22 of them with type 1, and 18 with type 2 retinal changes. The motor and sensory conduction veloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…7 Decrease in SNCV in this study is consistent with the observation of (Tupkovic E et al) that showed SNCV was higher in control group as compared to diabetics whereas there was no significant difference in conduction velocity of diabetics and control groups in MNCV. 8 The pathological mechanisms implicated in diabetic neuropathy, include micro-vascular damage, metabolic disorders, and changes in the interactions between neuronal and immunological systems in parallel with glial cell activation. Changes in the blood vessels supplying the peripheral nerves underlie the mechanisms involved in microvascular damage and hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…7 Decrease in SNCV in this study is consistent with the observation of (Tupkovic E et al) that showed SNCV was higher in control group as compared to diabetics whereas there was no significant difference in conduction velocity of diabetics and control groups in MNCV. 8 The pathological mechanisms implicated in diabetic neuropathy, include micro-vascular damage, metabolic disorders, and changes in the interactions between neuronal and immunological systems in parallel with glial cell activation. Changes in the blood vessels supplying the peripheral nerves underlie the mechanisms involved in microvascular damage and hypoxia.…”
Section: Discussionmentioning
confidence: 99%